Respostas fisiológicas de cultivares de cana-de-açúcar a herbicidas seletivos - Arantes, Marcel Tomás [UNESP]; Rhein, Andressa Freitas de Lima [UNESP]; Pincelli, Renata Passos [UNESP]; Silva, Marcelo de Almeida [UNESP] (My University, 2013)
The use of selective herbicides to control weeds has caused different responses in cultivars of sugar cane, and some products affect physiological characteristics and reduce the photosynthetic activity. This study aimed to evaluate the physiological traits in cultivars of sugar cane under the effect of applying post-emergence herbicides. The test was developed in Jau, SP. The experimental design was randomized blocks in factorial scheme 5 x 4 (cultivar x herbicide) with four replications. SP81-3250, RB855156, RB855453, RB867515, IACSP95-5000 were grown in this studied. Herbicides clomazone (1200 g i.a.ha-1); commercial mixture of clomazone + ametryn (1000 + 1500 g i.a.ha-1) and ametryn (3000 g i.a.ha-1) and a control were applied at 30 days after planting. Cultivars IACSP95-5000 and RB867515 were less affected physiologically and can be considered selective to these herbicides. The application of clomazone and ametryn affected negatively the traits maximum photochemical efficiency of photosystem II (Fv/Fm), SPAD index and photosynthetic pigments, but the mixture of these herbicides caused higher reductions, indicating to be the more aggressive to the cultivars.

A utilização de herbicidas seletivos no controle de plantas daninhas tem causado diferentes respostas em cultivares de cana-de-açúcar, e alguns produtos afetam as características fisiológicas e reduzem a atividade fotossintética. O presente trabalho teve como objetivo avaliar as variáveis fisiológicas de cultivares de cana-de-açúcar sob efeito da aplicação de herbicidas seletivos em pós-emergência. O ensaio foi desenvolvido em Jaú, SP. O delineamento experimental foi em blocos ao acaso, no esquema fatorial 5 x 4 (cultivares x herbicidas), com quatro repetições. Foram utilizadas as cultivares SP81-3250, RB855156, RB855453, RB867515, IACSP95-5000. Aos 30 dias após o plantio foram aplicados os herbicidas clomazone (1200 g.i.a. ha-1); mistura comercial de clomazone + ametryn (1000 + 1500 g.i.a. ha-1) e ametryn (3000 g.i.a. ha-1), além da testemunha sem aplicação. As cultivares IACSP95-5000 e RB867515 foram menos afetadas fisiologicamente, podendo ser consideradas seletivas aos herbicidas aplicados. Clomazone e ametryn afetaram negativamente as variáveis máxima eficiência fotoquímica do fotossistema II (Fv/Fm), índice SPAD e pigmentos fotossintéticos, porém a mistura desses herbicidas causou maiores reduções, indicando ser menos seletiva para as cultivares.
Physiological responses of sugarcane cultivars to selective herbicides
Keywords: Ametryn; Chlorophyll; Clomazone; Phytotoxicity; Saccharum spp; Selectivity